Phage display antibodies for diagnostic applications - Hairul Bahara N.H.; Tye G.J.; Choong Y.S.; Ong E.B.B.; Ismail A.; Lim T.S. (2024)
With major developments in molecular biology, numerous display technologies have been successfully introduced for recombinant antibody production. Even so, phage display still remains the gold standard for recombinant antibody production. Its success is mainly attributed to the robust nature of phage particles allowing for automation and adaptation to modifications. The generation of monospecific binders provides a vital tool for diagnostics at a lower cost and higher efficiency. The flexibility to modify recombinant antibodies allows great applicability to various platforms for use. This review presents phage display technology, application and modifications of recombinant antibodies for diagnostics. 2013 The International Alliance for Biological Standardization.